2020
DOI: 10.7554/elife.56502
|View full text |Cite
|
Sign up to set email alerts
|

Microglial calcium signaling is attuned to neuronal activity in awake mice

Abstract: Microglial calcium signaling underlies a number of key physiological and pathological processes in situ, but has not been studied in vivo in awake mice. Using multiple GCaMP6 variants targeted to microglia, we assessed how microglial calcium signaling responds to alterations in neuronal activity across a wide range. We find that only a small subset of microglial somata and processes exhibited spontaneous calcium transients in a chronic window preparation. However, hyperactive shifts in neuronal activity (kaina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
157
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 43 publications
13
157
1
Order By: Relevance
“…A growing body of evidence demonstrates that microglia influence neuronal excitability and seizure susceptibility ( Badimon et al, 2020 ; Umpierre et al, 2020 ; Wu et al, 2020 ). We found that excessive activation of mTOR in TSC1-deficient mice leads to severe spontaneous seizures, involving a noninflammatory mechanism ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence demonstrates that microglia influence neuronal excitability and seizure susceptibility ( Badimon et al, 2020 ; Umpierre et al, 2020 ; Wu et al, 2020 ). We found that excessive activation of mTOR in TSC1-deficient mice leads to severe spontaneous seizures, involving a noninflammatory mechanism ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…During application of exogenous glutamate or NMDA (N-Methyl-D-aspartate), microglial processes extend towards neurons; and this recruitment is dependent on activation of neuronal NMDA receptors and accompanying Ca 2+ influx, followed by ATP release from neurons and purinergic P2Y12 receptor-mediated stimulation on microglia [ 22 , 33 ]. Interestingly, a recent in vivo study has shown that a hyper- as well as a hypoactive state of the neural network can increase process outgrowth [ 34 ], indicating that any abnormal neuronal activity, irrespective of the direction of this abnormality, increases microglial process dynamics. Consistently, the dynamics of microglial surveillance is also changed by different kinds of anesthesia, known to modify neuronal activity [ 35 , 36 ].…”
Section: Functional Signature Of Young Adult Microgliamentioning
confidence: 99%
“…Intracellular Ca 2+ signaling is actively involved into both sensor and effector functions of microglia [ 34 , 43 , 44 , 45 ]. Due to technical reasons, however, it has long been challenging to study microglial Ca 2+ signaling in vivo.…”
Section: Functional Signature Of Young Adult Microgliamentioning
confidence: 99%
See 2 more Smart Citations